2018
DOI: 10.1089/hum.2018.027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of AAV Vector Tropisms for Mouse and Human Pluripotent Stem Cell–Derived RPE and Photoreceptor Cells

Abstract: Adeno-associated viral vectors are showing great promise as gene therapy vectors for a wide range of retinal disorders. To date, evaluation of therapeutic approaches has depended almost exclusively on the use of animal models. With recent advances in human stem cell technology, stem cell-derived retina now offers the possibility to assess efficacy in human organoids in vitro. Here we test six adeno-associated virus (AAV) serotypes [AAV2/2, AAV2/9, AAV2/8, AAV2/8T(Y733F), AAV2/5, and ShH10] to determine their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 53 publications
(61 reference statements)
3
75
0
Order By: Relevance
“…At the onset of stage 3, retinal organoids have attained an advanced state of PR development and organization, including formation of IS, OS and an ONL and OPL, making this stage optimal for modeling PR-based diseases. The presence of an OLM is also useful for investigating apical penetration of drug and gene delivery systems to PR cell bodies, given the correspondence of the surrounding culture medium to the anatomical subretinal space (Gonzalez-Cordero et al, 2018). However, PRs are also aberrantly located within the inner regions of stage 3 organoids where they lack ONL-like organization and are less accessible to culture Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of stage 3, retinal organoids have attained an advanced state of PR development and organization, including formation of IS, OS and an ONL and OPL, making this stage optimal for modeling PR-based diseases. The presence of an OLM is also useful for investigating apical penetration of drug and gene delivery systems to PR cell bodies, given the correspondence of the surrounding culture medium to the anatomical subretinal space (Gonzalez-Cordero et al, 2018). However, PRs are also aberrantly located within the inner regions of stage 3 organoids where they lack ONL-like organization and are less accessible to culture Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of AAV in human ROs is relatively limited at the moment, but studies have reported varying efficiency of transduction, which could be attributed to age of treatment, time of harvesting, vector tropisms, viral titre, the promotor used and sensitivity of detection of the transgene, e.g. antibody versus intrinsic fluorescence of a reporter (Gonzalez-Cordero et al, 2018, Tornabene et al, 2019, Quinn et al, 2019, Khabou et al, 2018. Here we demonstrate highly efficient transduction using an AAV2/5 vector with RP2 under the control of a CAG promoter.…”
Section: Discussionmentioning
confidence: 82%
“…This may be due to a combination of vector tropisms and the organization of the organoid, where the photoreceptor layer is outermost and thereby the first cells to contact the viral particles in solution, analogous to the situation following subretinal delivery. AAV RP2 was delivered at D140, prior to the onset of the increase in photoreceptor TUNEL reactivity and ONL thinning, but late enough to ensure efficient uptake, following reports of inefficient transduction at earlier time points (Gonzalez-Cordero et al, 2018). Not only was RP2 efficiently expressed at the mRNA and protein level, but it was also able to rescue the ONL thinning phenotype in RP2 KO retinal organoids implying a protective effect of RP2 overexpression in photoreceptor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To produce single stranded AAV9.CMV.hCLN6, the hCLN6 cDNA was cloned into a pD10 vector containing the CMV promoter as reported (19). Briefly, recombinant AAV2/9 was produced through a triple-transient transfection method and purified by size separation on a Sephacryl S300 column followed by anion exchange chromatography using a POROS 50 HQ column as previously described (30). Viral genome titers were determined by quantitative real-time PCR using a probe-based assay aligning to the SV40 poly-adenylation signal.…”
Section: Plasmid Construct and Recombinant Aav Productionmentioning
confidence: 99%